FAKTOR – FAKTOR YANG MEMPENGARUHI STATUS INDEKS KEBERSIHAN GIGI DAN MULUT (OHI-S) DI MASA PANDEMI COVID-19 PADA ANAK KELAS 3 DI SDN BOJONG 4 KABUPATEN CIANJUR (Poltekkes Kemenkes Bandung, 2022)
Dental and oral health is part of body health that inseparated from one another because dental and oral health will affect the health of the body. Maintenance of dental and oral hygiene was one of the efforts to improved dental and oral health. The high prevalence of dental and oral disease was strongly influenced by several factors, three of which are knowledge, attitudes and socio-economics. This type of research was quantitative analytic. The data collection technique used a cross sectional approach. The location of the research was SDN Bojong 4, Cianjur Regency, West Java with a total sample of 36 respondents. Data analysis was carried out by univariate, bivariate with Chi-Square. The results of the bivariate analysis of variables showed no significant relationship between OHI-S and knowledge of oral and dental hygiene (P= 0.057), attitude to maintaining oral hygiene (P=0.057) and socioeconomic status (P=0.22).